Perception of socio-environmental risks in land occupation of Playa Ancha, Valparaíso Chile. The cases of Pueblo Hundido and Vista al Mar - de Armas-Pedraza, Tania; Gascón Martín, Felipe; Muñoz Salazar, Patricia (Papeles de Población; Vol. 23 Núm. 93 (2017): Papeles de Población, 2017)
Land occupations are precarious and informal settlements where the poorest sectors of Latin American cities are installed. The article analyzes the territorial processes into two land occupations of Valparaiso (Chile) using the approach of vulnerability and social risk management. It aims to identify the meanings that people assign to the risks with which they live and try to identify the actions taken to prevent disasters. The results show feelings of marginalization and exclusion of the urban system. Also people are aware of the precariousness of the environment and the threats that surround them. However, they are not organized, relying on neighborhood solidarity to solve the problems. Only after the tragedy, they appealed to organization, without achieving its materialization.